Sobre el habla y las tradiciones populares de Segurilla - Hernando Cuadrado, Luis Alberto (Revista de Filología Románica, 2008)
El habla de Segurilla, being Segurilla a village located in the region of Talavera de la Reina, is the title of the Thesis that the autor wrote in order to get his University Degree. This Thesis was directed by Dr. Alonso Zamora Vicente during the school year 1972-1973. After several investigations about it, this last article offers a new actual view of the topic.